Embriogênese somática a partir de embriões zigóticos de urucu Bixa orellana L. - (:unkn) unknown (Museu Paraense Emílio Goeldi, 1993)
Seeds from ripe annatto fruits were washed in tap water and disinfected in 70% alcohol for 5 minutes, washed in sterile distilled water, then in 1% NaOCl for 15 minutes under agitation and washed three times in sterile distilled water in a laminar flow chamber. Embryos at the torpedo to adult stage were extracted and inoculated into Murashige & Skoog (MS) culture medium, added sucrose (3%), solidified with agar (0.7%) and different combinations of 2,4-D (0; 0.25; 0.5 and 1 mg/L) and activated carbon (0; 0.1 and 0.3%). The media were grown at 28 + 1°C, relative humidity 70% and photoperiod of 16 h light/day. The treatments had 30 replicates. Callus formation occurred at 15 days of incubation in all treatments, especially those with 0.1% activated carbon and absence of activated carbon, with 70% well-developed callus in the presence of mg/L (0.5 of 2,4-D + 0.5 Kin; 1 of 2,4 + 0.5 Kin). The calli then produced somatic embryos under the same culture conditions as MS medium in the absence of growth regulator. Seedlings were obtained on MS medium containing 1 mg/L AIB and 0.3% activated charcoal.
Somatic embryogenesis from zygotic embryos of annatto Bixa orellana L.
Keywords: Embriogênese; Urucu; CNPQ::CIENCIAS BIOLOGICAS::BOTANICA